1995
DOI: 10.1136/jcp.48.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Increased gastric production of interleukin-8 and tumour necrosis factor in patients with Helicobacter pylori infection.

Abstract: (J7 Clin Pathol 1995;48:133-136)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
98
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(105 citation statements)
references
References 20 publications
6
98
1
Order By: Relevance
“…In a study on circulating serum levels of IL-6, IL-8 and TNF-α in patients with H. pylori infection, there was not a significant difference in serum levels of TNF-α and age and gender between positive and negative H. Pylori groups (23), which is consistent with the results of our study. The results of this study and the study by Fan showed that the pathogen makes no significant change in serum levels of TNF-α (23,24). However, data from our study showed an increase in serum levels of IL-1β and TNF-α cytokines in people infected with H. pylori, in another study, the average of these two cytokines was significantly higher in infected group with H. pylori than non-infected individuals (22,25).…”
Section: Discussioncontrasting
confidence: 47%
“…In a study on circulating serum levels of IL-6, IL-8 and TNF-α in patients with H. pylori infection, there was not a significant difference in serum levels of TNF-α and age and gender between positive and negative H. Pylori groups (23), which is consistent with the results of our study. The results of this study and the study by Fan showed that the pathogen makes no significant change in serum levels of TNF-α (23,24). However, data from our study showed an increase in serum levels of IL-1β and TNF-α cytokines in people infected with H. pylori, in another study, the average of these two cytokines was significantly higher in infected group with H. pylori than non-infected individuals (22,25).…”
Section: Discussioncontrasting
confidence: 47%
“…7 Among these chemokines, interleukin-8 (IL-8), a prototype CXC chemokine, seems to play an important role in recruiting and activating neutrophils in the gastric mucosa. 8 Several reports suggest that gastric epithelial cells represent an important source of IL-8. 8,9 In addition to chemotactic potential, IL-8 is capable of activating polymorphonuclear leukocyte degranulation, the respiratory burst, and the 5-lipoxygenase pathway.…”
mentioning
confidence: 99%
“…8 Several reports suggest that gastric epithelial cells represent an important source of IL-8. 8,9 In addition to chemotactic potential, IL-8 is capable of activating polymorphonuclear leukocyte degranulation, the respiratory burst, and the 5-lipoxygenase pathway. 6 Thus, IL-8 may be a component of the inflammatory cascade.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, ROS activate signal transduction for the expression of inflammatory cytokines and chemokines ( 2 ). Interleukin-8 (IL-8), a member of the C-X-C chemokine family, is a potent chemoattractant and activator of neutrophils, monocytes, and T lymphocytes (3)(4)(5). ROS mediate the expression of IL-8 by activating oxidant-sensitive transcription factors in gastric epithelial cells (6)(7)(8).…”
mentioning
confidence: 99%